Assessing global-warming induced soil organic matter and iron oxides depletion: Empirical insights into sorption and uptake of atrazine by plants - Diagboya, Paul N.; Düring, Rolf-Alexander; Justus Liebig University Giessen (My University, 2024)
Recent pesticide use is alarmingly high and unregulated in several parts of the world. Pesticide fate in soil is controlled by sorption processes which affect the subsequent transport and chemical reactivity in the environment, as well as uptake by plants. Sorption processes are dependent on soil composition and properties, but these are beginning to be affected by global warming-linked factors leading to soil depletion. Thus, it is vital to decipher soils’ response, especially in the sub-Sahara (SS), to the depletion of some inherent components in the presence of pesticides. This was ascertained by monitoring a model pesticide (atrazine) sorption and desorption on whole SS soil (WS), and the same soil whose organic matter (OMR) and iron oxides (IOR) were substantially depleted, as well as studying atrazine uptake from these soils by fast-growing vegetables. Organic matter depletion enhanced equilibrium in OMR. Sorption was enhanced at lower ambient pH, higher initial atrazine concentration, and higher temperature. Hysteresis was low resulting in high desorption. Overall, atrazine desorption of ≥65 % was observed; it was higher in OMR (≥95 %) since SOM enhanced hysteresis. Though sub-Saharan soils are rich in iron oxides, SOM played a significantly higher role in sorption than iron oxides in this soil. This result suggests a high potential for atrazine to leach into the aquifer in the sub-Saharan. Atrazine uptake experiment by waterleaf and spinach showed that it could be detected in soil after 63 d, and its presence significantly affected the growth of both vegetables especially in soils with depleted SOM and iron oxides, and at high (100 µg/kg) atrazine spiking. Spinach may be a higher atrazine accumulator than waterleaf. It may be concluded that waterleaf and spinach grown on atrazine-contaminated soils, especially on SOM/iron oxide-depleted soils, are likely to accumulate atrazine.
Keywords: ddc:630